Identification of microRNAs and mRNAs associated with multidrug resistance of human laryngeal cancer Hep-2 cells - Wanzhong Yin (Brazilian Journal of Medical and Biological Research, 2013)
Multidrug resistance (MDR) poses a serious impediment to the success of chemotherapy for laryngeal cancer. To identify microRNAs and mRNAs associated with MDR of human laryngeal cancer Hep-2 cells, we developed a multidrug-resistant human laryngeal cancer subline, designated Hep-2/v, by exposing Hep-2 cells to stepwise increasing concentrations of vincristine (0.02-0.96 µM). Microarray assays were performed to compare the microRNA and mRNA expression profiles of Hep-2 and Hep-2/v cells. Compared to Hep-2 cells, Hep-2/v cells were more resistant to chemotherapy drugs (∼45-fold more resistant to vincristine, 5.1-fold more resistant to cisplatin, and 5.6-fold more resistant to 5-fluorouracil) and had a longer doubling time (42.33±1.76 vs 28.75±1.12 h, P<0.05), higher percentage of cells in G0/G1 phase (80.98±0.52 vs 69.14±0.89, P<0.05), increased efflux of rhodamine 123 (95.97±0.56 vs 12.40±0.44%, P<0.01), and up-regulated MDR1 expression. A total of 7 microRNAs and 605 mRNAs were differentially expressed between the two cell types. Of the differentially expressed mRNAs identified, regulator of G-protein signaling 10, high-temperature requirement protein A1, and nuclear protein 1 were found to be the putative targets of the differentially expressed microRNAs identified. These findings may open a new avenue for clarifying the mechanisms responsible for MDR in laryngeal cancer.